PENGARUH PENERAPAN STRATEGI E-COMMERCE DALAM MENINGKATKAN VOLUME PENJUALAN DI TENGAH MASA PANDEMI COVID 19 - Noorlaily Maulida; - Junaidi; - Periyadi (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2021)
Abstract, The main objective of this research is to study and analyze the effect of implementing e-commerce strategies in increasing the sales volume made by Indomaret partner SMEs in the peat area of Banjar Regency, South Kalimantan. This research was conducted with quantitative methods and using analysis methods with SPSS Windows For Data as a data analysis tool. The object of this research is the SME Partners Indomaret in the area of Peat District, Banjar Regency, South Kalimantan Province with 123 outlets and 100 outlets were taken as samples. The conclusion of the research shows that the technical variable (technique) has a greater influence than other variables, namely the variable Interface (X1), Navigation (X2), Content (X3) and Reliability (X4). Technical variable (technique) obtained t count of 8.708 with a significance value of 0.000, because the significance value is smaller than 0.06 (0.000 <0.06), and the regression coefficient has a positive value of 0.655.